PROPOSED SELECTION OF PVC PIPE PRODUCT SUPPLIERS IN TOKO BESI LANCAR REJEKI USING THE ANALYTICAL NETWORK PROCESS METHOD - Vanessa, Milka; Fransiscus, Hanky; Tjandra, Sugih Sudharma (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Toko Besi Lancar Rejeki is a shop that sells materials and equipment for building materials. This store was founded in 2003 and cooperates with several suppliers to supply some building materials. One of the items supplied is a pipe. Pipes are items that are quite often purchased. There is a main supplier that supplies PVC pipe product, namely Supplier A. However, there are some situations that make the store suffer losses, such as shipping errors made by the supplier and damage to the pipe which makes the store must return it to the supplier. Identification and decision-making processes are done using the Analytical Network Process (ANP) method which is based on the relationship between the criteria and sub-criteria. There are 6 criteria, 14 sub-criteria, and 10 relationships. The 6 criteria set are variety, price, quality, service, delivery, and flexibility. This assessment resulted in supplier selection priorities that can be carried out by Toko Besi Lancar Rejeki, namely Supplier C with a limiting value of 0.124982, for Supplier B it is 0.106648, and Supplier A it is 0.09128. Supplier selection is based on the priority sub-criteria obtained, namely the price of one pipe, pipe flexibility, and discounts.